2021
DOI: 10.1016/j.foodchem.2020.128229
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and phytochemical profiles and biological activities of Moringa oleifera Lam. edible parts from Guinea-Bissau (West Africa)

Abstract: Moringa oleifera is an edible medicinal plant used to fight malnutrition in Africa. In this study, M. oleifera flowers, fruits and seeds from Guinea-Bissau were characterized for their nutritional composition and hydroethanolic and aqueous extracts were prepared to investigate the phenolic profiles and bioactivities. Seeds presented higher levels of proteins (~31 g/100 g dw), fat (~26 g/100 g dw) and flavan-3-ol derivatives, while carbohydrates, proteins, citric acid, and glycosylated flavonoids were abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
0
25
1
1
Order By: Relevance
“…oleifera leaves did not affect viability of gilthead sea bream head‐kidney leukocytes after 24 h of exposure. Interestingly, in cancer cells, Fernandes et al, (2020) observed that different seed and flower hydroethanolic extracts could reduce proliferation and invasion. Similarly, M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…oleifera leaves did not affect viability of gilthead sea bream head‐kidney leukocytes after 24 h of exposure. Interestingly, in cancer cells, Fernandes et al, (2020) observed that different seed and flower hydroethanolic extracts could reduce proliferation and invasion. Similarly, M .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, M . oleifera is a good source of secondary metabolites and has contributed to therapeutic, biological and medicinal properties (Fernandes et al, 2020). Particularly, its seed kernels possess anti‐inflammatory and antimicrobial activities (Jaja‐Chimedza et al, 2017), as well as defensive effects against rheumatoid arthritis (Mahajan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This takes advantage of the effects of oats, flaxseed and soya on the normalization of the lipidic and glycemic profile, through their chemical and nutritional composition, providing strategies for the nutritional management and prevention of obesity, DM2, dyslipidemia/CVD and MS [ 61 , 104 , 105 , 106 , 107 ]. These functional foods and their different bioactive properties related to NTCDs can be associated with the nutrients present in M. oleifera , which presents excellent nutritional potential and broad pharmacological properties [ 20 , 31 , 108 , 109 ]…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…That is because M. oleifera is rich in macro and micronutrients [ 57 , 149 , 150 , 151 ]. The plant is also considered to be a moderately adequate source of calcium, niacin (B3), protein, essential amino acids (threonine, valine, methionine, leucine, isoleucine, phenylalanine, histidine, lysine and arginine) and dietary fiber [ 57 , 108 , 149 , 152 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation